Practical Issues of Health Data Processing According to General Data Protection Regulation - Januševičienė, Justina (Teisė, 2018)
The aim of the Member States of the European Union to find a balance among main freedoms, granted by the European Union, technological progress, the interests of public security and the rights of individuals was accomplished with the adoption of Regulation (EU) 2016/679 of the European Parliament and of the council on the protection of natural persons with regard to the processing of personal data and on the free movement of such data, and repealing Directive 95/46/EC (General Data Protection Regulation). It is believed that besides important data protection novelties, with are being introduced by General Data Protection Regulation, it’s provisions will help to achieve significant progress in international cooperation in the field of lifesciences and healthcare, which were restricted due to disparities among countries concerning personal health data for a while. The article focuses on questions whether General Data Protection Regulation brings in enough legal clarity and legal certainty into healthcare, which is bound by the principle of subsidiarity. The article also deals with practical aspects of application of personal health data processing provisions of General data protection regulation.